The thermal, rheological and structural properties of cassava starch granules modified with hydrochloric acid at different temperatures - Beninca, Cleoci; Colman, Tiago André Denck; Lacerda, Luiz Gustavo; Filho, Marco Aurélio Silva Carvalho; Bannach, Gilbert [UNESP]; Schnitzler, Egon (Elsevier, 2013)
Starch is arguably one of the most actively investigated biopolymer in the world. In this study, the native (untreated) cassava starch granules (Manihot esculenta, Crantz) were hydrolyzed by standard hydrochloric acid solution at different temperatures (30 °C and 50 °C) and the hydrolytic transformations were investigated by the following techniques: simultaneous thermogravimetry-differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), as well as non-contact atomic force microscopy (NC-AFM), X-ray diffraction (XRD) powder patterns, and rapid viscoamylographic analysis (RVA). After the treatment with hydrochloric acid at different temperatures, the thermal stability, a gradual loss of pasting properties (viscosity), alterations in the gelatinization enthalpy (ΔHgel), were observed. The use of NC-AFM and XRD allowed the observation of the surface morphology and topography of the starch granules and changes in crystallinity of the granules, respectively. © 2012 Elsevier B.V. All rights reserved.
Keywords: Cassava starch; DSC; Gelatinization; NC-AFM; TG-DTA; Viscoamylogram; Atomic force microscopy; Differential scanning calorimetry; Differential thermal analysis; Gelation; Granulation; Hydrochloric acid; Plants (botany); Thermogravimetric analysis; X ray diffraction; Starch